2019
DOI: 10.21203/rs.2.17035/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification of loci associated with growth in rainbow trout

Abstract: Background Growth is a major economic production trait in aquaculture. Improvements in growth performance will reduce time and cost for fish to reach market size. However, genes underlying growth have not been fully explored in rainbow trout.Results A 50K, gene-transcribed SNP chip was used for genotyping a total of 789 fish with available phenotypic data for bodyweight gain. Genotyped fish were obtained from two consecutive generations produced in the NCCCWA growth-selection breeding program. Weighted single-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
4
12
0
Order By: Relevance
“…Aguilar et al (2019) showed that the highest peak based on the p-value was not the same based on the proportion of variance explained, and this is because the latter depends on allele frequency, i.e., high effect but low frequency decreases the variance explained [97]. This result is consistent with other studied traits, such as fillet firmness, protein content [20], and bodyweight gain [98] in rainbow trout.…”
Section: Unique Genes Affecting the Additive Genetic Variance For Moisupporting
confidence: 76%
“…Aguilar et al (2019) showed that the highest peak based on the p-value was not the same based on the proportion of variance explained, and this is because the latter depends on allele frequency, i.e., high effect but low frequency decreases the variance explained [97]. This result is consistent with other studied traits, such as fillet firmness, protein content [20], and bodyweight gain [98] in rainbow trout.…”
Section: Unique Genes Affecting the Additive Genetic Variance For Moisupporting
confidence: 76%
“…Increased knowledge of the genetic basis of muscle quality traits will facilitate to advance the commercial breeding in salmonids. GWA studies are powerful tools to identify genetic variants associated with complex traits [36,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…A 50K transcribed SNP-chip, suitable for GWA analyses, has been recently developed in our laboratory. The array has been used to identify large-effect QTL responsible for genetic variance in fillet yield, firmness, protein content, and body weight gain using the same fish population used in this study [36,39,40]. The current study aimed to identify QTL associated with the additive genetic variance in fillet fat and moisture content for the same rainbow trout population.…”
Section: Introductionmentioning
confidence: 99%
“…The selective breeding program has been established in 2004 and underwent five generations of selection for body weight. Details on how the population was formed and selected for growth can be found in [8,54]. The trimmed fillet was weighed, and fillet yield was calculated as a percent of whole-body weight.…”
Section: Fish Population and Phenotypesmentioning
confidence: 99%